SCIENCE AND TECHNOLOGICAL ASPECTS IN RELIGIOUS RITUALS IN THE WOMEN FARMERS GROUP OF JEMPIRING KABUPATEN BADUNG, BALI, INDONESIA - Suryathi, Ni Wayan; Antara, Made; Atmaja, Nengah Bawa; Windia, Wayan (International Journal of Biosciences and Biotechnology, 2018)
This study aims to analyse the science and technological values in religious rituals in the women farmers group of Jempiring Kabupaten Badung. The data was analysed qualitatively. The results show: science and technological values in religious rituals which are implemented through Tri Hita Karana which are harmonious relationship with God, harmonious relationship with other people, and harmonious relationship with the environment, it is evident from Banten Pejati that is complete with segehan Agung which is given on piodalan at Pura Melanting. Ans it is also followed by pemerastitaan and pelukatan rituals for the group’s members. Daksina in Banten Pejati is the symbol of God’s palace. This symbol provides a scientific-psycho-theological effect that makes the minds of the people moored in the presence of a metaphysical god in the support of physical daksina. This value is also found in the sound of kul-kul, genta, gamelan, kidung and mantra during rituals. A harmonious relationship with other people is also seen from the behavior of good and honest members with a basis of menyame braya.